Statistical Test of Two Way Anova Block Design as a Decision Making Tool for Analyzing the Growth Results of Staphylococcus aureus Bacteria in Sorghum Media (Sorghum bicolor L. Moench) - Sri Sulami Endah Astuti; Diah Titik Mutiarawati (Health Notions, 2022)
Statistics has wide uses for making the right decisions in various areas of life, because statistics give a person the knowledge and ability to evaluate data. Through this research, researchers hope to create a new learning model from the results of the development of the Two Way Anova Design Block Statistical Test that can be used as a decision-making tool in the analysis of data on the growth results of Staphylococcus aureus bacteria on alternative media from sorghum media. The results obtained in this study, that in the variation of the sorghum period 4 grams, 5 grams, and 6 grams both in dilution with aqua distillation and meat broth the growth of Staphylococcus aureus bacteria in contrast to the growth in mannitol salt agar (positive control) media. Meanwhile, in the periodic variation of 7 grams of sorghum in both aqua distillation and meat broth, there is no difference in the growth in mannitol salt agar media. Two way Anova block design, used if the experimental material is grouped. So that each group aranges a replication for the treatment. The treatment was given randomly to each group. Based on statistical method approach block design, we find alternative mannitol salt agar media into sorghum.